Edukasi Pengetahuan Alat Pelindung Diri Pada Pekerja Universitas Nahdlatul Ulama Surabaya - Afandi, Afandi Sudarmawan; Ligoy, Friska Ayu; Toba, Nafis Damanhuri; Sunaryo, Merry (Lembaga Dongan Dosen, 2023)
A university is a form of further education institution called a college and has faculties, within these faculties there are various departments or study programs. Workers with a healthy, safe and comfortable body and environment are what all workers want. The physical environment of the workplace and organizational environment is very important in influencing social, mental and physical, Occupational Safety and Health or what is often shortened to K3 is an effort to create a comfortable and safe working environment in order to achieve a goal, namely increasing worker productivity. . The main factor causing accidents is usually caused by the humans themselves, namely in the form of actions that neglect or ignore superiors' instructions not to use PPE while working. The purpose of this activity is to provide education on the application of OSH and the importance of using PPE. This research used the pre-test and post-test methods directly to 15 employees and 5 students. then given a pre test to find out knowledge about PPE, after completing the pre test it is continued with socialization after completing the post test to find out the understanding and knowledge of employees and students. The employees and students of Nadlaatul Ulama University in Surabaya got a score of 84.5 before the socialization and then after the socialization they got a score of 98. So this shows that the socialization that was carried out was said to be successful.